2022
DOI: 10.1002/advs.202105158
|View full text |Cite
|
Sign up to set email alerts
|

Ionically Conductive Tunnels in h‐WO3 Enable High‐Rate NH4+ Storage

Abstract: Compared to the commonly applied metallic ion charge carriers (e.g., Li + and Na + ), batteries using nonmetallic charge carriers (e.g., H + and NH 4 + )generally have much faster kinetics and high-rate capability thanks to the small hydrated ionic sizes and nondiffusion control topochemistry. However, the hosts for nonmetallic charge carriers are still limited. In this work, it is suggested that mixed ionic-electronic conductors can serve as a promising host for NH 4 + storage. Using hexagonal tungsten oxide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
36
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(40 citation statements)
references
References 38 publications
4
36
0
Order By: Relevance
“…Small redox peaks are observed at low rates (Figure S5), which probably can be ascribed to the redox reactions for NH 4 + upon insertion/extraction in the α‐MoO 3 structure. Similar results have been reported for h ‐WO 3 , [24] but not h ‐MoO 3 [2a] . The corresponding GCD curves (Figure 3b) reveal that the capacity of this electrode is 107 mAh g −1 (∼117 mAh cm −3 ) at 0.2 A g −1 .…”
Section: Resultssupporting
confidence: 90%
“…Small redox peaks are observed at low rates (Figure S5), which probably can be ascribed to the redox reactions for NH 4 + upon insertion/extraction in the α‐MoO 3 structure. Similar results have been reported for h ‐WO 3 , [24] but not h ‐MoO 3 [2a] . The corresponding GCD curves (Figure 3b) reveal that the capacity of this electrode is 107 mAh g −1 (∼117 mAh cm −3 ) at 0.2 A g −1 .…”
Section: Resultssupporting
confidence: 90%
“…30 Zhang et al also confirmed that tunnel h -WO 3 has a better NH 4 + storage capacity than m -WO 3 . 31 Although the above studies have preliminarily confirmed that metal oxides with tunnel structure have excellent NH 4 + storage performance. However, it has poor structural stability during charge storage, and is prone to dissolve in (weakly) acidic aqueous solutions, resulting in abnormal structural collapse.…”
Section: Introductionmentioning
confidence: 90%
“…(ii) Using layered metal oxide electrodes with large interlayer sites to achieve high capacity through the interlayer topological chemistry of NH4 + , such as Ti 3 C 2 MXenes, 28 metal oxides (V 2 O 5 , 21 NH 4 V 4 O 10 , 29 MnO x , 20 and MoO 3 Zhi's group reported the tunnel structure of the h-MoO 3 anode and proposed that there is reversible NH 4+ intercalation/de-intercalation and formation/ fracture of H bonds in the tunnel structure, and it exhibits fast electrode dynamics 30. Zhang et al also conrmed that tunnel h-WO 3 has a better NH 4 + storage capacity than m-WO 3 31. The prepared (NH 4 ) x WO 3 //MnO 2 A-HSCs exhibit an ultrahigh areal capacitance of 2239.7 mF cm À2 at 2 mA cm À2 , and a wide operating voltage window of 0-1.8 V. They also delivered an outstanding areal energy density of 1010.1 mWh cm À2 and a peak areal power density of 18.0 mW cm À2 .…”
mentioning
confidence: 99%
“…Moreover, tungsten trioxide (WO 3 ) is an abundant, versatile oxide and has been widely applied for catalysis, batteries, and electrochemical devices due to its intrinsic properties and unique characteristics for chemical/structural modifications. [35,36] WO 3 is also notable for its ability to intercalate different metal atoms to improve its performance. [37] For example, Mo-doped W 18 O 49 nanowires showed sevenfold higher catalytic activity than that of pristine W 18 O 49 .…”
Section: Introductionmentioning
confidence: 99%